Preferred Alignments of Angular Momentum Vectors of Galaxies in the SDSS Supercluster S[202-001+0084] - Malla, Janak Ratna; Aryal, Binil; Saurer, Walter (NUTA Journal, 2019)
We present a study of spin vector orientation of 1331 SDSS (Sloan Digital Sky Survey) galaxies in SDSS Supercluster S[202-001+0084] having redshift 0.02 to 0.03. The data are provided by our collaborator, Institute of Astro-particle Physics, Innsbruck University, Austria. We have converted two dimensional data to three dimensional by Godlowskian Transformation. Our aim is to find out non-random effects in the preferred alignments of angular momentum vectors of galaxies. In general, no preferred alignments angular momentum vectors of galaxies are noticed, supporting Hierarchy model of galaxy formation. In almost all sub samples the 1st order Fourier coefficient suggests that the angular momentum vectors are randomly oriented but other statistical tests suggest anisotropic distribution probably due to the binning effect and gravitational shearing effect.